Isolation of the Fathead Minnow Nidovirus from Muskellunge Experiencing Lingering Mortality. Issue 2 (26th May 2016) - Faisal, Mohamed; Baird, Ashley; Winters, Andrew D.; Millard, Elena V.; Marcquenski, Sue; Hsu, Hui‐Min; Hennings, Ann; Bochsler, Phil; Standish, Isaac; Loch, Thomas P.; Gunn, Michelle R.; Warg, Janet
Abstract: In 2011, the Fathead Minnow nidovirus (FHMNV; Genus Bafinivirus, Family Coronaviridae, Order Nidovirales ) was isolated from pond‐raised juvenile Muskellunge Esox masquinongy suffering from lingering mortality at the Wild Rose Hatchery in Wild Rose, Wisconsin. Moribund Muskellunge exhibited tubular necrosis in the kidneys as well as multifocal coalescing necrotizing hepatitis. The FHMNV was also isolated from apparently healthy juvenile Muskellunge at the Wolf Lake State Fish Hatchery in Mattawan, Michigan. The identity of the two syncytia‐forming viruses (designated MUS‐WR and MUS‐WL from Wild Rose Hatchery and Wolf Lake State Fish Hatchery, respectively) as strains of FHMNV was determined based on multiple‐gene sequencing and phylogenetic analyses. The pathogenicity of the MUS‐WL FHMNV strain was determined by experimentally infecting naive juvenile Muskellunge through intraperitoneal injection with two viral concentrations (63 and 6.3 × 10 3 TCID50 /fish). Both doses resulted in 100% mortality in experimentally infected fish, which exhibited severely pale gills and petechial hemorrhaging in eyes, fins, and skin. Histopathological alterations in experimentally infected fish were observed mainly in the hematopoietic tissues in the form of focal areas of necrosis. Phylogenetic analysis of concatenated partial spike glycoprotein and helicase gene sequences revealed differences between the MUS‐WL FHMNV, MUS‐WR FHMNV, and two other FHMNV originally isolated from moribund Fathead Minnows Pimephales promelas including the index FHMNV strain (GU002364). Based on a partial helicase gene sequence, a reverse transcriptase PCR assay was developed that is specific to FHMNV. These results give evidence that the risks posed to Muskellunge by FHMNV should be taken seriously. Received May 1, 2015; accepted February 8, 2016